1967
DOI: 10.1042/bj1020065
|View full text |Cite
|
Sign up to set email alerts
|

The action of aflatoxin B1 on the rat liver

Abstract: The administration of a single dose of aflatoxin B(1) to the rat (7mg./kg. body wt.) results in the slow development of a periportal necrosis. Hepatic enzymes are released into the serum in the second 24hr. of the poisoning, closely preceding the onset of the necrosis, which is followed by a rise in serum alkaline-phosphatase activity and bilirubin concentration. Aflatoxin B(1) has been detected in the nucleus of the poisoned liver cell and in vitro it has been shown to interact with DNA. The toxin inhibits th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
5

Year Published

1968
1968
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(39 citation statements)
references
References 32 publications
3
31
0
5
Order By: Relevance
“…It is, therefore, easy to understand the activity of these polysomes in v i m . This hypothesis is in agreement with the results of Clifford et al [4] who also found no differences between biological activity in v i m of polysomes treated with aflatoxin in vivo and control polysomes. However, with liver slices these authors showed a specific inhibition of protein synthesis by aflatoxin-treated polysomes.…”
Section: Biological Activity Of Treated Polysomessupporting
confidence: 93%
“…It is, therefore, easy to understand the activity of these polysomes in v i m . This hypothesis is in agreement with the results of Clifford et al [4] who also found no differences between biological activity in v i m of polysomes treated with aflatoxin in vivo and control polysomes. However, with liver slices these authors showed a specific inhibition of protein synthesis by aflatoxin-treated polysomes.…”
Section: Biological Activity Of Treated Polysomessupporting
confidence: 93%
“…Furthermore, histological studies on the sequential alterations produced by AFB (Butler, 1964) and fluorescence microscopic studies on the cellular localization of this carcinogen (Stora et al, 1979;Stora, 1980) have been reported. However, the AFBinduced liver biochemical changes reported previously were confined to the initial fewv days of the acute injury stage (Shank & Wogan, 1966;Svoboda et al, 1966;Clifford & Rees, 1967). Since available information does not establish the correlation between sequential biochemical and histological changes in rats treated with AFB, we have undertaken an investigation of the sequential effects of the toxin on the biochemical parameters in the serum and the biochemical and histological characters in the liver of rats for a period of 28 days after a single dose.…”
mentioning
confidence: 88%
“…Alterations of serum, inorganic phosphorus, glucose, cholesterol and albumin are shown in Table III (Wogan, 1968(Wogan, , 1969Akinrimisi et al, 1974;Yu, 1977). However, studies of AFB action on protein synthesis and protein content in the rat liver have yielded contradictory results (Clifford & Rees, 1967;Shank & Wogan, 1966;VillaTrevino & Leaver, 1968;Ramachandra Pai et al, 1978). In concerning the effect of AFB on liver protein content, some reported no significant effect (Shank & Wogan, 1966) but Ramachandra Pai et al (1978) showed a significant decrease on Day 1 after dosing.…”
Section: Body Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…It inhibits phospholipid synthesis in rat liver (Clifford & Rees, 1967) and labelled acetate incorporation into rat liver cholesterol (Kato, Onoda & Omori, 1969), and phospholipids, cholesterol and neutral fats of human skin (Black, Smith, Austin & Rauschkolb, 1970). It has also been demonstrated (Tung, Donaldson & Hamilton, 1972) that dietary aflatoxin decreases serum triglyceride fatty acids, total phospholipids and cholesterol levels in chickens.…”
Section: Aflatoxinmentioning
confidence: 99%